1999
DOI: 10.1111/j.1479-828x.1999.tb03393.x
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Presentation of Gestational Trophoblastic Disease

Abstract: We report a case of gestational trophoblastic disease leading to an acute abdomen due to a haemoperitoneum in a young multipara.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…However, detection of hCG in a symptomatic older, postmenopausal woman strongly suggests the diagnosis of latent GTT. Although we had the opportunity to see four heterogeneous presentations of invasive moles, many other unusual presentations have been reported in the past [6][7][8][9][10]. Our experience showed that a high index of suspicion should be kept in women with H/O abortion and irregular bleeding.…”
Section: Discussionmentioning
confidence: 96%
“…However, detection of hCG in a symptomatic older, postmenopausal woman strongly suggests the diagnosis of latent GTT. Although we had the opportunity to see four heterogeneous presentations of invasive moles, many other unusual presentations have been reported in the past [6][7][8][9][10]. Our experience showed that a high index of suspicion should be kept in women with H/O abortion and irregular bleeding.…”
Section: Discussionmentioning
confidence: 96%